Target interaction profiling of midostaurin and its metabolites in neoplastic mast cells predicts distinct effects on activation and growth - Peter, Barbara; Schwaab, Juliana; Reiter, Andreas (Leukemia, 2016)
Proteomic-based drug testing is an emerging approach to establish the clinical value and anti-neoplastic potential of multikinase inhibitors. The multikinase inhibitor midostaurin (PKC412) is a promising new agent used to treat patients with advanced systemic mastocytosis (SM). We examined the target interaction profiles and the mast cell (MC)-targeting effects of two pharmacologically relevant midostaurin metabolites, CGP52421 and CGP62221. All three compounds, midostaurin and the two metabolites, suppressed IgE-dependent histamine secretion in basophils and MC with reasonable IC50 values. Midostaurin and CGP62221 also produced growth inhibition and dephosphorylation of KIT in the MC leukemia cell line HMC-1.2, whereas the second metabolite, CGP52421, which accumulates in vivo, showed no substantial effects. Chemical proteomic profiling and drug competition experiments revealed that midostaurin interacts with KIT and several additional kinase targets. The key downstream regulator FES was recognized by midostaurin and CGP62221, but not by CGP52421 in MC lysates, whereas the IgE receptor downstream target SYK was recognized by both metabolites. Together, our data show that the clinically relevant midostaurin metabolite CGP52421 inhibits IgE-dependent histamine release, but is a weak inhibitor of MC proliferation, which may have clinical implications and may explain why mediator-related symptoms improve in SM patients even when disease progression occurs.